Better Students Ask More Questions.
Multiply the radicals: ³√x^4 y * ³√x^2 y^2Please show solution with everything...
1 Answer | add yours
Notice that the radicals have like orders, hence you may multiply the like variables under radicals such that:
`(x^4*y)*(x^2*y^2) = x^(4+2)*y^(1+2)`
`(x^4*y)*(x^2*y^2) = x^6*y^3`
You need to evaluate the cube root such that:
`root(3)(x^6*y^3) = (x^6*y^3)^(1/3)`
`root(3)(x^6*y^3) = x^(6/3)*y^(3/3)`
`root(3)(x^6*y^3) = x^2*y`
Hence, multiplying the cube roots yields `root(3)((x^4*y))*root(3)((x^2*y^2))=x^2*y.`
Posted by sciencesolve on May 3, 2012 at 5:27 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.